2006
DOI: 10.1007/s00204-006-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating from animal studies to the efficacy in humans of a pretreatment combination against organophosphate poisoning

Abstract: The extrapolation from animal data to therapeutic effects in humans, a basic pharmacological issue, is especially critical in studies aimed to estimate the protective efficacy of drugs against nerve agent poisoning. Such efficacy can only be predicted by extrapolation of data from animal studies to humans. In pretreatment therapy against nerve agents, careful dose determination is even more crucial than in antidotal therapy, since excessive doses may lead to adverse effects or performance decrements. The commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Although we did not characterize each extract for secondary metabolites, it might be possible that the inhibitory effect comes from thymoquinone as it did show a similar pattern to various extracts. As the present study was carried out in vitro on two animal models, the extrapolation to the expected pharmacological effects in humans might be considered more reliable (Levy et al ., ). Consequently, attention should be paid to the possible drug interaction in patients who concurrently use N .…”
Section: Resultsmentioning
confidence: 97%
“…Although we did not characterize each extract for secondary metabolites, it might be possible that the inhibitory effect comes from thymoquinone as it did show a similar pattern to various extracts. As the present study was carried out in vitro on two animal models, the extrapolation to the expected pharmacological effects in humans might be considered more reliable (Levy et al ., ). Consequently, attention should be paid to the possible drug interaction in patients who concurrently use N .…”
Section: Resultsmentioning
confidence: 97%
“…Previously in humans, caramiphen was taken orally at up to 1.15 mg/kg or 3.4 mg/kg over 4 days, which led to peak blood level of 60 ng/ml (Levandoski and Flanagan, 1980;Tallarida, 1982). Levy et al (2007) extrapolated from dogs and monkeys to predict an effective dose of caramiphen against 1.6-1.8 LD 50 sarin in humans to be 70-100 ng/ml. Our study aimed to bring about higher blood levels of caramiphen, in this range, for this later therapeutic intervention against GD exposure in our rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know the blood and brain concentrations of caramiphen after in vivo injection of 100 mg·kg −1 of body weight. If we attempt to make a very rough estimate based on the blood concentrations of caramiphen after repeated or continuous administration (Levandoski and Flanagan, 1980; Levy et al ., 2007), we would suggest that a single injection of 100 mg·kg −1 caramiphen produced a blood concentration in the micromolar range. It is likely, therefore, that the NMDA receptor‐antagonistic properties of caramiphen contributed to its anticonvulsant efficacy; previous studies have suggested that antagonism of NMDA receptors plays an important role in the termination of nerve agent‐induced seizures (Braitman and Sparenborg, 1989; Dorandeu et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%